MEMPERKUAT PERAN MAHASISWA PARIWISATA DALAM MEMBUDAYAKAN GERAKAN ANTI KORUPSI - Vina Dini Pravita (Sekolah Tinggi Pariwisata Ambarrukmo Yogyakarta, 2022)
Indonesia is aggressively suppressing corruption, one of which is by strengthening the role of tourism students in cultivating the anti-corruption movement. The number of corruption cases in Indonesia should not be carried out by the younger generation in the future. This study aims to describe the steps that can be taken to strengthen the role of tourism students in cultivating the anti-corruption movement. The method used in this research is literature study. The results of this study are obtained several ways that can be done, namely by adding anti-corruption material to college courses, holding seminars, case discussions, campaigns to the regeneration of anti-corruption students. The anti-corruption movement also needs support from tourism colleges and law enforcement so that the anti-corruption culture is understood and interpreted by students more deeply.Keywords: Tourism Students, Anti-Corruption Movement, Tourism Colleges